Dampak Pemilihan Model Spin-Off Unit Usaha Asuransi Syariah terhadap Tingkat Efisiensi - Syah, Firman; Arianty, Erny (IAIN Kudus, 2024)
The Sharia Insurance Business Unit (UUS), which has implemented a spin-off using the model of forming a new company, has reduced the company's level of operational efficiency. However, the acquisition model has never been tested. This research analyzes the efficiency and profit growth level of UUS's implementation of spin-offs using an acquisition model. The research method used is quantitative with a Data Envelopment Analysis (DEA) approach. The research results show that the efficiency level for companies that spin off using an acquisition model, in this case, PT Adira Dinamika Tbk, experiences a decline in both the efficiency of assets and expenses to underwrite income and assets and operating expenses to net profit. The implication of this research for the industry is to provide considerations for the industry in deciding on the appropriate spin-off model and determining the necessary strategies. Theoretical implications, this research provides enrichment related to spin-offs, especially the link between the selection of the Spin-off model and efficiency.